Effective Treatment of Bovine Mastitis with Intramammary Infusion of Angelica dahurica and Rheum officinale Extracts. (3rd March 2019) - Yang, Wan-Ting; Ke, Chun-Yen; Wu, Wen-Tien; Lee, Ru-Ping; Tseng, Yi-Hsiung
Abstract : Mastitis in dairy cattle is a highly prevalent infectious disease, causing considerable economic loss worldwide. In this study, we used Angelica dahurica and Rheum officinale extracts (designated as Yi-Xiong-Tang, YXT) for mastitis treatment. California mastitis test (CMT) was performed and 67 mastitis udder quarters were identified among 179 lactating dairy cows. These 67 mastitis udder quarters were subjected to treatments by intramammary infusion of YXT twice a day for three consecutive days. The mastitis indicators including clots, lactate dehydrogenase (LDH), TNF- α, IL-6, IL-8, and total viable count of bacteria (TVC) in milk were examined before and after the YXT treatment to evaluate its effectiveness. Levels of mastitis indicators from mastitis udder quarters were elevated. After YXT treatment, normal levels of these indicators were restored: TVC, 2.10 × 10 4 – 9.20 × 10 6 CFU/mL; clots, 6.56 ± 0.43 mg/mL; LDH, 181.0 ± 18.55 U/L; TNF- α, 0.02 ± 0.02 ng/mL; IL-6, 41.4 ± 11.46 pg/mL; and IL-8, 1.85 ± 0.60 pg/mL. Compared with the antibiotic therapy, YXT treatment has a shorter treatment course and might have lower probability for the causative agents to develop drug resistance because YXT is in fact a cocktail containing multiple active ingredients.